Depression and Quality of Life among the Chronic Kidney Disease Patients - Kunwar, Dipak; Kunwar, Rajyashree; Shrestha, Barsha; Amatya, Richa; Risal, Ajay (Journal of Nepal Health Research Council, 2020)
Background: Depression and other mental illness are very common among chronic kidney disease and also Quality of life has been found significantly impaired in chronic kidney disease. The objective of our study is to study Depression, Quality of life and its associations in chronic kidney disease. Methods: This was a descriptive cross-sectional study. We used convenient method of sampling for data collection. The World Health Organization Quality-of-Life 8-question scale was used for estimating quality of life and Beck Depression Inventory was used for the assessment of depression. Independent samples t-test was conducted to analysed bivariate relationship of sociodemographic factors with depression and Quality of life scores and multiple linear regression analysis was performed to determine predictors of Quality of life. Results: The 75.5% participants found to have depression. Depression was found statistically significant across socioeconomic status (p value 0.04) and other medical comorbidities (p value 0.04). Variables found to be significantly associated with total quality of life in multiple linear regression analysis were caste (p value 0.03), socioeconomic status (p value 0.009) and depression (p value 0.001). Conclusions: Depression and reduced quality of life is very common among chronic kidney patients. Low socioeconomic status and comorbid medical conditions were associated with depression and caste, low socioeconomic status and depression were associated with low quality of life. Screening and management of depression should be included in the routine care and it could help improving the quality of life of patients with chronic kidney disease. Keywords: chronic kidney disease; depression; quality of life